2022
DOI: 10.1021/acs.jproteome.1c00904
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Differential Preservation of Bone Proteomes in Inhumed and Entombed Cadavers from Italian Forensic Caseworks

Abstract: Bone is a hard biological tissue and a precious reservoir of information in forensic investigations as it retains key biomolecules commonly used for identification purposes. Bone proteins have recently attracted significant interest for their potential in estimating post-mortem interval (PMI) and age at death (AAD). However, the preservation of such proteins is highly dependent on intrinsic and extrinsic factors that can hinder the potential application of molecular techniques to forensic sciences. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
16

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 63 publications
1
17
0
16
Order By: Relevance
“…However, a previous study has reported by using correction for multiple testing there was a high risk of generating false negatives as the ratio compression in TMT-labeling quantitative proteomics studies, few replicates and a limited reproducibility between individuals even replicates [44]. Therefore, many clinical proteomics studies still used Student's t-test instead of multiple testing corrections [45,46]. In order to increase the reliability of our proteomics results, we used western blotting to confirm the expressions of one upregulated protein PRDX2, one downregulated protein MARCO, and one unchanged protein VCAM1, of which results were consistent with proteomics data.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study has reported by using correction for multiple testing there was a high risk of generating false negatives as the ratio compression in TMT-labeling quantitative proteomics studies, few replicates and a limited reproducibility between individuals even replicates [44]. Therefore, many clinical proteomics studies still used Student's t-test instead of multiple testing corrections [45,46]. In order to increase the reliability of our proteomics results, we used western blotting to confirm the expressions of one upregulated protein PRDX2, one downregulated protein MARCO, and one unchanged protein VCAM1, of which results were consistent with proteomics data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, being induced by BMP2 from bone-forming cells (Gori et al 2001), FMOD significantly attenuates the osteoclast precursor maturation, suggesting its coupling role in osteoblast–osteoclast crosstalk (Kram et al 2020). A recent bone proteomic study in inhumed and entombed cadavers of Italian forensic casework revealed a slight decrease in FMOD in aging bones (Bonicelli et al 2022). Thus, FMOD plays a positive role in bone development and maintenance.…”
Section: Fmod Is Involved In Diverse Tissue Development and Regenerationmentioning
confidence: 99%
“…Large-scale unbiased analytical techniques, such as transcriptomics, proteomics, metabolomics, and lipidomics, are powerful methods that are often used to gain comprehensive insights into complex biological systems and their changes in aging and diseases. Several successful transcriptomics and single-cell-sequencing efforts have been undertaken in bones [37][38][39], but few quantitative bone proteomic studies have been published [40][41][42][43][44][45]. Given the structural relevance of extracellular matrix (ECM) proteins and signaling peptides within the skeleton, analyzing bone proteome profiles during aging and age-related skeletal biology will be highly beneficial and insightful.…”
Section: Introductionmentioning
confidence: 99%